Blendas à base de quitosana e poliacrilamida revestidas com ZnO como catalisadores para a fotodegradação do azul de metileno - MAIA, Luziane Freire (2017)
Textile dyes are recognized as a serious environmental problem due the huge quantity discharged annually in water environments, and its dangerous health risks. Efficient and low cost methods for effluent treatment and recovery of impacted areas are necessary and increasingly researched. The photocatalytic degradation is one of these methods, and this work investigated the feasibility of photocatalytic degradation of the methylene blue (AM) dye from aqueous solutions (5 and 15 mgL-1) in the presence and absence of prepared catalysts (chitosanpolyacrylamide (QT-P), and chitosan-polyacrylamide doped with Zn, QT-P/ZnO). The chitosan and polyacrylamide interaction was studied as a function of the degree of deacetylation of chitosan (64, 82 and 90%), previously obtained from the deacetylation of chitin extracted from shrimp exoskeletons. The QT-P/ZnO heterostructures were characterized by FTIR, XRD and MEV. The photocatalysis experiments were performed considering the effects of pH, contact time and mass variation. AM samples were irradiated with mercury vapor lamp (black light,50W mm-2) and photocatalysis was monitored by UV-Vis spectrophotometry, at the peak wavelength of 665 nm. The results indicated that QT-P interaction is favored by deacetylation. All the materials prepared showed a catalytic effect, but the heteroestructure obtained from the chitosan with the highest degree of deacetylation (QTC-P/ZnO) was the most efficient: 99.2% (AM, 15 mg L-1, 50 min) and 99.8% (AM, 5 mg L-1, 20 min).